Community-Based Pre-Disaster Abrasion Mitigation Strategy in the Coastal Area of Nibung Village, Paloh District - Suherdiyanto Suherdiyanto; Adhitya Prihadi (MASI Mandiri Edukasi, 2026)
Coastal abrasion poses significant risks to shoreline stability, infrastructure, and the socio-economic life of coastal communities, yet community-based mitigation efforts often remain fragmented and short-term. This study aims to analyze community-based pre-disaster mitigation strategies for coastal abrasion in Nibung Village, examine the role of the village government, and assess the level of community and youth participation in risk reduction efforts. The research employs a qualitative case study approach, with data collected through field observations, semi-structured interviews, documentation, and limited questionnaires using purposive sampling. Informants include village officials, community leaders, affected residents, and students involved in environmental activities. Data were analyzed using an interactive model supported by triangulation techniques. The findings reveal that the community demonstrates adequate awareness of abrasion risks, informed by lived experiences. Mitigation efforts include temporary embankment construction, mangrove planting, awareness campaigns, and active involvement of community members and students. However, these initiatives remain short-term and are not yet integrated into formal village development planning. Key challenges include limited funding, insufficient technical capacity, and weak institutional coordination. Strengthening collaborative governance and embedding community-based mitigation into long-term planning are essential for achieving sustainable coastal protection.